SORPTION CHARACTERISTICS OF THE SOFT BANGKOK CLAY - L. Sthapit; C. S. P. Ojha; U. Glawe (Lowland Technology International, 2005)
Asian countries are in a need for identification of suitable sites for disposal of municipal solid wastes. The travel of pollutants is significantly influenced by the properties of the porous medium through which these travel. In Thailand, existing land disposal sites, which were initially selected in view of the low lying areas or the water bodies, are likely to last not for many years. In the light of this, it is essential that soils available in the region are tested and evaluated for their specific characteristics relevant to the safe disposal of solid wastes and planning of future landfill sites. Sorption characteristics are of special significance in the design of landfills. In this paper, the Bangkok clay has been evaluated for its sorption characteristics. Various adsorption isotherm models are tested and it has been observed that the Langmuir model performs best. The study indicates that the process of sorption is non-linear in nature and is sensitive to the type of influent characteristics.